2015
DOI: 10.1121/1.4930563
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between speech segment duration and vowel centralization in a group of older speakers

Abstract: This study examined the relationship between average vowel duration and spectral vowel quality across a group of 149 New Zealand English speakers aged 65 to 90 yr. The primary intent was to determine whether participants who had a natural tendency to speak slowly would also produce more spectrally distinct vowel segments. As a secondary aim, this study investigated whether advancing age exhibited a measurable effect on vowel quality and vowel durations within the group. In examining vowel quality, both flexibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 23 publications
2
24
0
1
Order By: Relevance
“…On the other hand, findings from studies on the acoustic and articulatory variability across the age would support the view that the observed age-related rhythmic changes might be due to reasons other than diminished oro-facial strength or neuro-muscular degeneration [30]- [32]. [30], for example, found that older speakers with longer average vowel durations also tended to produce more acoustically distinct vowels.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…On the other hand, findings from studies on the acoustic and articulatory variability across the age would support the view that the observed age-related rhythmic changes might be due to reasons other than diminished oro-facial strength or neuro-muscular degeneration [30]- [32]. [30], for example, found that older speakers with longer average vowel durations also tended to produce more acoustically distinct vowels.…”
Section: Discussionmentioning
confidence: 78%
“…[30], for example, found that older speakers with longer average vowel durations also tended to produce more acoustically distinct vowels. From an articulatory viewpoint, there is evidence that the slower speech is not imputable to constrained lip, jaw movements in older adults [31]- [32].…”
Section: Discussionmentioning
confidence: 99%
“…According to Bilodeau-Mercure and Tremblay (2016), indeed, older adults reduce their speech rate to compensate for the decrease in lip and jaw stiffness when asked to produce speech at fast and very fast rates. From an acoustic point of view, for example, Fletcher and McAuliffe (2015) found that New Zealand English speakers aged over 65 tended to speak with longer average vowel durations as well as to produce more acoustically distinct vowels. Based on this, we might tentatively interpret the reduced segment/ vowel and consonant rate in Chomsky' speech in view of his attempt to keep his pronunciation clear while giving public speeches.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, vowel lengthening does not necessarily entail vowel space expansion (see e.g. Fletcher et al, 2015). Despite the partial independence of vowel duration and articulation, there is a commonly used research strategy which treats changes in duration, vowel space size, and articulatory range as dierent manifestations of a single gradient phenomenon, commonly referred to as phonetic reduction and phonetic enhancement (or strengthening).…”
Section: Introductionmentioning
confidence: 99%